Video self instruction method to improve self esteem - Febriyani, Tika; Mawarni, Anisa; Subandi, Subandi (Universitas Islam Negeri Raden Intan Lampung, 2022)
Self-esteem ability is really needed based on the data from the distribution of the instrument, there are 61.6% of students who do not love themselves and have low self-esteem abilities and 90.4% feel the need for efforts to increase self-esteem abilities The aim of this study was to produce a method of counseling services that can increase individual self-esteem. This research used research and development methods or